Thyroid Dysfunction and Cardiovascular Abnormalities in a Young Patient with Turner Syndrome - Amin, MR; Rana, S; Hossain, AR; Mohammad, H; Chowdhury, MAW; Kahhar, MA (Journal of Armed Forces Medical College, Bangladesh, 2011)
DOI: http://dx.doi.org/10.3329/jafmc.v7i1.8628 JAFMC Bangladesh. Vol 7, No 1 (June) 2011; 46-49